1966
DOI: 10.1071/ar9660543
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the diet of the grazing animal. I. Seasonal changes in the diet of sheep grazing on pastures of different availability and composition

Abstract: The diet of grazing sheep was studied by using animals with oesophageal fistulas. Seasonal changes in the botanical and chemical composition of the diet when grazing Phalaris–annual grasses–subterranean clover pasture are described. The effect of grazing intensity on diet is considered. A comparison was made of diets on seven pasture species. None of the species examined had a useful qualitative superiority over Phalaris either in winter or in summer, when the digestibility of this species declines considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Rangeland in low condition classes may require more protein supplement for longer periods due to the reduced diversity of high-quality plants and inadequate forage quantity. also reported that CP content of sheep diets was not limiting to animal production (Arnold et al 1966;Bedell 1971;Wilson 1976).…”
Section: Results and Discussion Crude Proteinmentioning
confidence: 93%
“…Rangeland in low condition classes may require more protein supplement for longer periods due to the reduced diversity of high-quality plants and inadequate forage quantity. also reported that CP content of sheep diets was not limiting to animal production (Arnold et al 1966;Bedell 1971;Wilson 1976).…”
Section: Results and Discussion Crude Proteinmentioning
confidence: 93%
“…clover) in the diet against . its proportion in the sward (Meyer et al 1957;Weir &Torell 1959;Arnold 1960Arnold , 1987Wilson 1963;Van Dyne & Heady 1965;Arnold et al 1966;Grimes et al 1966;Bedel 1968Bedel , 1973Hamilton et al 1973;Leigh & Holgate 1978;Briseno & Wilman 1981;Milne et al 1982;Clark & Harris 1985;Curll et al 1985). A major problem with this approach, particularly if the real aim is to measure preference, lies in estimating the proportion of that item that is available to the sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Some data from continuously grazed swards suggest that grass and clover are distributed in a similar manner from the top of the sward (Johnson et al 1989). Also, Arnold et al (1966) tested diet selection under continuous grazing throughout 2 years of study and found essentially no difference between the proportion of clover in the diet and that in the sward (see also Grimes et al 1966;Arnold 1987; but see Bedell 1968). Furthermore, Milne et a/.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major increase in lignin content occurs when plants change from the elongation stage to the reproductive stage (Chen et al 2002). Vegetation containing high ADF values have lower digestible energy concentration and can restrict dry matter intake, ultimately decreasing the amount of energy cattle receive (Arnold et al 1966;Moore and Jung 2001). Therefore, aspen suckers, with ADF levels never exceeding 28% provided a higher quality diet that meets energy demands of cattle.…”
Section: Discussionmentioning
confidence: 96%